2020
DOI: 10.1186/s12906-020-03171-4
|View full text |Cite
|
Sign up to set email alerts
|

Purple-leaf tea (Camellia sinensis L.) ameliorates high-fat diet induced obesity and metabolic disorder through the modulation of the gut microbiota in mice

Abstract: Background Obesity and its associated diseases have become a major world-wide health problem. Purple-leaf Tea (Camellia sinensis L.) (PLT), that is rich of anthocyanins, has been shown to have preventive effects on obesity and metabolic disorders. The intestinal microbiota has been shown to contribute to inflammation, obesity, and several metabolic disorders. However, whether PLT consumption could prevent obesity and diet-induced metabolic diseases by modulating the gut microbiota, is not clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…Although many studies on the anti-obesity effect of dark tea's fermented substances have been conducted (24), no specific mechanism-related studies have been conducted on the antiobesity effect of dark tea. In this study, the effect of suppressing obesity was confirmed through various evaluation indicators by administering dark tea candidate substances to obesity-induced mice through high-fat diets, and the mechanism of the antiobesity effect was analyzed using the target tissue.…”
Section: Anti-obesity Effects Of Dark Tea Extracts By Down-regulation...mentioning
confidence: 99%
“…Although many studies on the anti-obesity effect of dark tea's fermented substances have been conducted (24), no specific mechanism-related studies have been conducted on the antiobesity effect of dark tea. In this study, the effect of suppressing obesity was confirmed through various evaluation indicators by administering dark tea candidate substances to obesity-induced mice through high-fat diets, and the mechanism of the antiobesity effect was analyzed using the target tissue.…”
Section: Anti-obesity Effects Of Dark Tea Extracts By Down-regulation...mentioning
confidence: 99%
“…In addition, it increased total fecal SCFAs, in particular propionic acid and valeric acid [ 74 ]. Powdered leaves of purple-leaf tea, a new cultivar of C. sinensis with purple leaves, also mitigated the negative effects of an HFD on the murine gut microbiome [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…rich in anthocyanins prevented the effects of obesity and metabolic disorders and prevented microbial dysbiosis in C57BL/6J mice HFD‐fed with purple tea for 10 weeks. Purple tea increased the diversity of the microbiota and attenuated the rise of the F / B ratio caused by the HFD; moreover, the families Barnesiellaceae , Ruminococcaceae , and Lachnospiraceae , together with the genus Barnesiella , increased compared to HFD alone 83 . The administration of Angelica keiskei juice to HFD‐fed C57BL/6 mice prevented weight gain, decreased fat accumulation, blood glucose, serum lipid levels, and normalized gut dysbiosis.…”
Section: Effects Of Polyphenol‐rich Foods On the Gut Microbiota Dysbi...mentioning
confidence: 93%
“…Purple tea increased the diversity of the microbiota and attenuated the rise of the F / B ratio caused by the HFD; moreover, the families Barnesiellaceae , Ruminococcaceae , and Lachnospiraceae , together with the genus Barnesiella , increased compared to HFD alone. 83 The administration of Angelica keiskei juice to HFD‐fed C57BL/6 mice prevented weight gain, decreased fat accumulation, blood glucose, serum lipid levels, and normalized gut dysbiosis. Angelica keiskei had various flavonoids, among which coumarins, phenolic acids, chalcones, and terpenoids; chalcones (xanthoangelol and 4‐hydroxyderricin) are considered the major components.…”
Section: Effects Of Polyphenol‐rich Foods On the Gut Microbiota Dysbi...mentioning
confidence: 99%